2004
DOI: 10.1111/j.1365-2265.2004.02041.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma adiponectin levels in newborns are higher than those in adults and positively correlated with birth weight

Abstract: OBJECTIVE The aim of this study was to examine plasma adiponectin concentrations during perinatal the period and their correlations with fetal anthropometric parameters and other hormones. DESIGN Venous cord blood samples were obtained from 59 full-term healthy newborns (36 males and 23 females, gestational age 37·0 -41·4 weeks, birth weight 2,146 -4,326 g, birth length 44·0 -54·5 cm). The blood samples were also obtained from 15 neonates (postnatal day 3 -7) whose cord blood had already been collected and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
141
3
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(164 citation statements)
references
References 40 publications
16
141
3
4
Order By: Relevance
“…Observations of raised adiponectin levels in relation to increased urine albumin excretion in girls but not in boys in our study may be important as, in addition to insulin resistance, factors influencing adiponectin levels such as age [15,16], sex [17] and puberty [18] are also associated with risk of microalbuminuria during adolescence [19].…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Observations of raised adiponectin levels in relation to increased urine albumin excretion in girls but not in boys in our study may be important as, in addition to insulin resistance, factors influencing adiponectin levels such as age [15,16], sex [17] and puberty [18] are also associated with risk of microalbuminuria during adolescence [19].…”
Section: Discussionmentioning
confidence: 48%
“…It is possible that adiponectin levels may not simply reflect levels of insulin resistance in type 1 diabetes. Complex changes in adiponectin levels are seen during childhood, as levels are higher in the newborn period [15] and fall through puberty [16]. Clear sex-related differences have been identified, with higher levels in girls than in boys during early childhood [17] and puberty [18].…”
Section: Introductionmentioning
confidence: 99%
“…11 Recent studies have shown that cord blood adiponectin concentrations are correlated positively with birth weight, suggesting that fetal adiponectin levels are likely to influence fetal growth. 8,10,27,28 MazakiTovi et al 29 have reported that the cord blood adiponectin concentration in the smaller neonate of discordant twins is lower than that in the larger counterpart. Our result showing that cord blood adiponectin concentrations were positively correlated with birth weight s.d.…”
Section: Adiponectin Snps and Cord Blood Adiponectin M Saito Et Almentioning
confidence: 99%
“…Furthermore, we confirmed previous findings of no gender difference in adiponectin levels. 8,10,11,28 Serum adiponectin levels are known to be inversely correlated with body fat mass in adolescents and adults, whereas cord blood adiponectin concentrations are positively correlated with birth weight s.d. score, mostly determined by fat mass.…”
Section: Adiponectin Snps and Cord Blood Adiponectin M Saito Et Almentioning
confidence: 99%
“…In adults, adiponectin concentration is inversely related to adiposity, but its association with adiposity is poorly understood (9,11,13). Some studies indicate a positive correlation between cord plasma adiponectin concentration and adiposity in infants (8,12,14,(16)(17)(18)(19)(20) and some have found no significant correlation (9,15).…”
Section: G Estational Diabetes Mellitus (Gdm) Is Impairedmentioning
confidence: 99%